Sindbis-Group Alphavirus Replication in Periosteum and Endosteum of Long Bones in Adult Mice - Heise, Mark T. (American Society for Microbiology, 2000)
Several alphaviruses, including the Sindbis-group viruses, Ross River virus, O'nyong-nyong virus, and Chikungunya virus, are associated with outbreaks of acute and persistent arthralgia and arthritis in humans. Mechanisms underlying alphavirus-induced arthralgia and arthritis are not clearly understood, though direct viral replication within or around the affected joints is thought to contribute to disease. S.A.AR86 is a Sindbis-group alphavirus closely related to the arthralgia-associated Ockelbo and GirdwoodS.A viruses. Following inoculation with S.A.AR86 derived from a molecular clone, infectious virus was isolated from bone and joint tissue 1 to 6 days postinfection. Studies using either in situ hybridization or S.A.AR86-derived double promoter viruses and replicons expressing green fluorescent protein localized sites of viral replication to the periosteum, tendons, and endosteum within the epiphyses of the long bones adjacent to articular joints. These results demonstrate that alphaviruses associated with arthralgia in humans replicate within bone-associated connective tissue adjacent to articular joints in an adult mouse model.